Enhanced production of IL-10 by dendritic cells deficient in CIITA. - Yee, C; Yao, Y; Xu, Q; McCarthy, B; Sun-Lin, D; Tone, M; Waldmann, H; Chang, C (2005)
Dendritic cells (DC) are professional APCs that play a critical role in regulating immunity. In DC, maturation-induced changes in MHC class II expression and Ag presentation require transcriptional regulation by CIITA. To study the role of CIITA in DC, we evaluated key cell functions in DC from CIITA-deficient (CIITA(-/-)) mice. The ability to take up Ag, measured by fluid phase endocytosis, was comparable between CIITA(-/-) and control DC. Although CIITA(-/-) DC lack MHC class II, they maintained normal expression of costimulatory molecules CD80, CD86, and CD40. In contrast, CIITA(-/-) DC activated with LPS or CpG expressed increased IL-10 levels, but normal levels of TNF-alpha and IL-12 relative to control. Enhanced IL-10 was due to greater IL-10 mRNA in CIITA(-/-) DC. Abeta(-/-) DC, which lack MHC class II but express CIITA normally, had exhibited no difference in IL-10 compared with control. When CIITA was cotransfected with an IL-10 promoter-reporter into a mouse monocyte cell line, RAW 264.7, IL-10 promoter activity was decreased. In addition, reintroducing CIITA into CIITA(-/-) DC reduced production of IL-10. In all, these data suggest that CIITA negatively regulates expression of IL-10, and that CIITA may direct DC function in ways that extend beyond control of MHC class II.